Variations in Lithospheric Thickness Across the Denali Fault and in Northern Alaska. Issue 24 (22nd December 2022) - Gama, Isabella; Fischer, Karen M.; Dalton, Colleen A.; Eilon, Zachary
Abstract: While variations in crustal structure beneath the Denali fault in Alaska are well‐documented, the existence of fault‐correlated structures throughout the entire thickness of the continental lithosphere is not. A new model of shear‐wave velocity structure obtained through joint inversion of surface wave and converted body wave data shows a northward increase in lithospheric thickness and velocity occurring across the Denali fault system. In northern Alaska, a dramatic increase in lithospheric thickness at the southern margin of the Arctic‐Alaska terrane lies in the vicinity of the Kobuk fault system. These correlations support the view that transpressive deformation tends to localize at the margins of thicker, higher‐strength lithosphere. Plain Language Summary: Major faults in Earth's tectonic plates, such as Alaska's Denali fault, begin as brittle fractures of the shallow crust and progress to include ductile shearing of the deeper crust. Changes in tectonic plate thickness or internal temperature have been observed beneath some faults, consistent with feedback between the strength of the deeper plate and the location of the fault. Using global earthquake signals, we built a new 3‐D model of seismic velocity structure throughout Alaska, extending from the surface to hundreds of kilometers in depth. According to the model, the Denali fault coincides with a northward thickening and an apparent abrupt temperature increase within Alaska's plate. Further north, at another boundary between geological provinces near the Kobuk fault, we also find an abrupt thickening of the plate. These relationships are consistent with faults being located near the edges of thicker, stronger regions of the tectonic plates. Key Points: A new model of seismic shear‐wave velocity beneath Alaska was obtained by jointly inverting surface wave and Sp body wave data The Denali fault lies just south of the margin of thicker and higher velocity upper plate lithosphere, as does the Kobuk fault These results support the view that gradients in lithospheric strength can be key to the localization of major continental strike‐slip faults